Influence of Public Private Partnerships on Performance of Projects Among State Corporations in Kenya - Mwatika, Mary Mkamburi; Shalle, Dr. Noor (International Journal of Supply Chain and Logistics, 2020)
Purpose: The overall objective of this study was to examine the influence of public private partnerships on performance of projects among state corporations in Kenya. Methodology: This research study adopted a descriptive research design approach. The study preferred this method because it allowed an in-depth study of the subject. The study employed stratified random sampling technique in coming up with a sample size of 127 respondents from a total of 187 target population. Structured and semi structured questionnaires were used to collect data. Data gathered from the questionnaires administered was analyzed by the help of Ms Excel and SPSS version 22, while output was presented inform of frequency tables and charts. The study used both descriptive and inferential statistics to show the relationship between variables. Results and conclusion: The regression equation above has established that taking all factors into account (policy framework, feasibility studies, value for money and risk mitigation) constant at zero, performance of projects among state corporations will be an index of 1.967. The study found that a unit increase in feasibility studies will lead to a 0.358 increase in the performance of PPP projects among state corporations. The P-value was 0.000 and hence the relationship was significant since the p-value was lower than 0.05. The findings presented also shows that taking all other independent variables at zero, a unit increase in policy framework will lead to a 0.132 increase in the performance of PPP projects among state corporations. The P-value was 0.02 which is less 0.05 and thus the relationship was significant. In addition, the study found that a unit increase in value for money will lead to a 0.121 increase in the performance of PPP projects among state corporations. The P-value was 0.000 and thus the relationship was significant because the p-value was less than 0.05. The study also found that a unit increase in risk mitigation will lead to a 0.05 increase in performance of PPP projects among state corporations. The P-value was 0.03, which is less than 0.05 and thus the relationship was significant. The findings of the study indicated that policy framework, feasibility studies, value for money and risk mitigation have a positive relationship with performance of projects among state corporations in Kenya. Unique contribution to theory, practice and policy: The study recommended that public institutions should embrace public private partnerships so as to improve performance of projects among state corporations and further researches should to be carried out in other public institutions to find out if the same results can be obtained.